2013
DOI: 10.1080/09712119.2013.783481
|View full text |Cite
|
Sign up to set email alerts
|

GnRHa active immunity regulates expression of LHR protein and development of uteri in ewes

Abstract: To investigate the LHR protein expressions in the ovine uteri and LH secretion, and to determine whether the alarelin active immunity affects the uterine development in ewes. Twenty-eight ewes (five to six months) were assigned to four experimental groups. Animals in EG-1, EG-2 and EG-3 were subcutaneously injected with 200, 300 and 400 mg alarelin antigens (day 0 and 14), respectively. Animals in the CG were injected with 2.0 mL solvent (day 0 and 14). Uterine horns were dissected aseptically on day 70. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The results demonstrated that Triptorelin treatment enhanced the expression of FSHR and LHR proteins in ovaries of mice. It was consistent with studies in ducks (Ni et al, 2007) and ewes (Lopot et al, 2008;Wei et al, 2013b) following alarelin (a GnRH agonist) immunization. The probable reasons may be that Cetrorelix treatment inhibited expressions of pituitary GnRHR mRNA and protein and protein in the rat (Horvath et al, 2002;Mo et al, 2010).…”
Section: Effects On Expression Levels Of Fshr and Lhr Proteins In Ovasupporting
confidence: 90%
See 1 more Smart Citation
“…The results demonstrated that Triptorelin treatment enhanced the expression of FSHR and LHR proteins in ovaries of mice. It was consistent with studies in ducks (Ni et al, 2007) and ewes (Lopot et al, 2008;Wei et al, 2013b) following alarelin (a GnRH agonist) immunization. The probable reasons may be that Cetrorelix treatment inhibited expressions of pituitary GnRHR mRNA and protein and protein in the rat (Horvath et al, 2002;Mo et al, 2010).…”
Section: Effects On Expression Levels Of Fshr and Lhr Proteins In Ovasupporting
confidence: 90%
“…To evaluate the expression levels of LHR and FSHR proteins in the ovary following Cetrorelix and Triptorelin active immunization, Western blotting was implemented referring to the previous description (Wei et al, 2013b). The relative contents of LHR and FSHR proteins were presented as the ratio between gray values of LHR and FSHR divided by that of b-actin.…”
Section: Western Blotting Analysis Of Fshr and Lhr Proteins In Ovariesmentioning
confidence: 99%
“…FSH receptor binding inhibitor peptide (FRBI, an 8-peptide including H-Ter-Glu-Asn-Leu-Glu-Pro-Asn-Gly-Glu-Gly-NH 2 ) of 99.9% purity was synthesized by Nanjing Peptide Biotech Co. Ltd., China (CAS: 163973-98-6) referring to initial reports (13) and characterized before using. FRBI solution was prepared according to the method established in our laboratory (19). The concentration of FRBI was 1 mg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the expression levels of ARID1A and PTEN genes and proteins in mice ovaries, western blot was carried out according to our previous report (19). The polyclonal antibodies of rabbit anti-ARID1A antibody-C-terminal (Ab176395; 1:2000), anti-PTEN antibody (Ab170941, Abcam Trade Co., China; 1:2000), and anti-FSHR antibody (BOSTER Biological Technology Co. Ltd, China; 1:1000) were utilized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation